Sustainable Industrial Sotol Production in Mexico - A Life Cycle Assessment - Madrid Solórzano, Juan Manuel (2022)
Sotol is a distilled spirit made in the north of Mexico. Although it received the badged Designation of Origin (DO) in 2002 and has an economic influence on the DO region, its environmental profile has not been figured out. For that reason, this paper reports a life cycle analysis (LCA) of the industrial sotol production process in the Mexican state of Chihuahua to find significant environmental impacts caused by sotol production from raw material acquisition to the packaging stage. The LCA was modeled using the SimaPro 8.5.2 LCA software, and the environmental impacts were calculated using the CML-IA baseline v3.03/EU25 impact assessment technique. Findings reveal that sotol beverage manufacturing considerably affects three of the eleven impact categories selected, and the harvest and bottling stages have the greatest negative environmental impact of all the sotol production stages. According to empirical data, one bottle (750 ml) of sotol results in a higher carbon dioxide value than any other spirit evaluated in earlier LCA studies. Sotol distillery might decrease road transport and change the primary packaging material type as strategies to achieve cleaner production.